Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2015
Podaj pierwiastki trójmianu kwadratowego i zapisz go w postaci ogólnej 4.71 gwiazdek na podstawie 7 opinii

Podaj pierwiastki trójmianu kwadratowego i zapisz go w postaci ogólnej

1Zadanie
2Zadanie
3Zadanie
4Zadanie
1Zadanie
2Zadanie

`a)` 

`x+10=0\ \ \ l u b \ \ \ x-20=0` 

`x=-10\ \ \ \ \ \ l u b\ \ \ x=20` 

 

`y=(x+10)(x-20)=x(x-20)+10(x-20)=` 

`\ \ \ =x^2-20x+10x-200=x^2-10x-200` 

 

 

`b)` 

`x-1/2=0\ \ \ l u b\ \ \ x-1/3=0` 

`x=1/2\ \ \ \ \ \ \ \ l u b \ \ \ x=1/3` 

 

`y=6(x-1/2)(x-1/3)=` `(6x-3)(x-1/3)=` 

`\ \ \ =6x(x-1/3)-3(x-1/3)=` 

`\ \ \ =6x^2-2x-3x+1=` `6x^2-5x+1` 

 

 

 

`c)` 

`x+3=0\ \ \ l u b\ \ \ 3x-4=0` 

`x=-3\ \ \ \ \ \ l u b \ \ \ 3x=4` 

`\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=4/3=1 1/3` 

 

`y=2(x+3)(3x-4)=` `(2x+6)(3x-4)=` 

`\ \ \ =2x(3x-4)+6(3x-4)=` 

`\ \ \ =6x^2-8x+18x-24=` 

`\ \ \ =6x^2+10x-24` 

 

 

 

`d)` 

`x-2/5=0\ \ \ l u b \ \ \ x+2/5=0` 

`x=2/5\ \ \ \ \ \ \ \ l u b \ \ \ x=-2/5` 

 

`y=5(x-2/5)(x+2/5)=` `(5x-2)(x+2/5)=` 

`\ \ \ =5x(x+2/5)-2(x+2/5)=` 

`\ \ \ =5x^2+2x-2x-4/5=` `5x^2-4/5` 

 

 

 

 

`e)` 

`2x-4=0\ \ \ l u b \ \ \ 2x-1=0` 

`2x=4\ \ \ \ \ \ \ \ l u b \ \ \ 2x=1` 

`x=2\ \ \ \ \ \ \ \ \ \l u b \ \ \ x=1/2` 

 

`y=(2x-4)(2x-1)=2x(2x-1)-4(2x-1)=` 

`\ \ \ =4x^2-2x-8x+4=` `4x^2-10x+4` 

 

 

 

`f)` 

`2x+1=0\ \ \ l u b \ \ \ 3x+1=0` 

`2x=-1\ \ \ \ \ l u b \ \ \ 3x=-1`  

`x=-1/2\ \ \ \ \ \l u b \ \ \ x=-1/3`  

 

`y=(2x+1)(3x+1)=2x(3x+1)+1(3x+1)=` 

`\ \ \ =6x^2+2x+5x+1=` `6x^2+7x+1` 

 

 

 

`g)` 

`5x-2=0\ \ \ l u b \ \ \ 4x-3=0`  

`5x=2\ \ \ \ \ \ \ \ l u b \ \ \ 4x=3`   

`x=2/5\ \ \ \ \ \ \ \ l u b \ \ \ \ x=3/4` 

 

`y=(5x-2)(4x-3)=` `5x(4x-3)-2(4x-3)=` 

`\ \ \ =20x^2-15x-8x+6=` `20x^2-23x+6` 

 

 

 

`h)` 

`2-3x=0\ \ \ l u b \ \ \ x+4=0` 

`2=3x\ \ \ \ \ \ \ \ l u b \ \ \ x=-4` 

`x=2/3` 

 

`y=(2-3x)(x+4)=2(x+4)-3x(x+4)=` 

`\ \ \ =2x+8-3x^2-12x=` `-3x^2-10x+8` 

 

 

 

`i)` 

`x=0\ \ \ l u b\ \ \ x+3=0` 

`\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=-3` 

 

`y=-x(x+3)=-x^2-3x` 

 

 

 

`j)` 

`1/2x=0\ \ \ l u b\ \ \ 2x-1=0` 

`x=0\ \ \ \ \ \ l u b \ \ \ 2x=1`  

`\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=1/2` 

 

`y=1/2x(2x-1)=x^2-1/2x` 

 

 

 

`k)` 

`7-3x=0\ \ \ l u b\ \ \ x=0` 

`7=3x` 

`x=7/3=2 1/3` 

 

`y=(7-3x)x=7x-3x^2=-3x^2+7x`     

        

 

 

`l)` 

`2x+3=0` 

`2x=-3` 

`x=-3/2=-1 1/2` 

 

`y=(2x+3)^2=(2x)^2+2*2x*3+3^2=` 

`\ \ \ =4x^2+12x+9`